2020
DOI: 10.7249/rra134-4
|View full text |Cite
|
Sign up to set email alerts
|

American Instructional Resources Surveys: 2020 Technical Documentation and Survey Results

Abstract: he RAND American Educator Panels (AEP) consist of the American Teacher Panel (ATP) and the American School Leader Panel (ASLP). These panels are nationally representative samples of K-12 public school educators. The ATP includes more than 25,000 teachers, and the ASLP includes more than 7,500 school principals. Both groups respond to numerous online survey requests each year. The AEP began in 2014 and expanded significantly during the 2016-2017 and 2017-2018 school years (Robbins and Grant, 2020).Since 2014, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 3 publications
1
17
1
Order By: Relevance
“…Another recommendation relates to differences in perspectives about the NGSS-and what standards teachers and schools are using-across states. While our study showed minimal variability across states, the findings from the data collected in the AIRS (Doan et al, 2020) demonstrates that many teachers may see themselves as teaching the NGSS, even if they are in a state that neither adopted nor adapted their standards based on the NGSS. While not explicitly related to public support for the NGSS, what standards teachers see themselves and their school as teaching may have a strong bearing on their support for the reform.…”
Section: Recommendations For Future Researchcontrasting
confidence: 58%
“…Another recommendation relates to differences in perspectives about the NGSS-and what standards teachers and schools are using-across states. While our study showed minimal variability across states, the findings from the data collected in the AIRS (Doan et al, 2020) demonstrates that many teachers may see themselves as teaching the NGSS, even if they are in a state that neither adopted nor adapted their standards based on the NGSS. While not explicitly related to public support for the NGSS, what standards teachers see themselves and their school as teaching may have a strong bearing on their support for the reform.…”
Section: Recommendations For Future Researchcontrasting
confidence: 58%
“…During the pandemic, teacher leavers in our sample reported working an average of 52 hours per week, and one-third of pandemic teachers said that they worked 56 hours or more per week during COVID-19. Our survey data corroborate findings from other recent teacher surveys that have found that teachers' working hours have increased during the pandemic (Diliberti and Kaufman, 2020;Doan et al, 2020).…”
Section: Notwithstanding the Challenges About Half Of Those Who Left ...supporting
confidence: 90%
“…Some of the items about current political topics were drawn from Education Week surveys (Lieberman, 2021;Najarro, 2021). Others were drawn from the American Instructional Resources Surveys (Doan et al, 2021) and the RAND Civic Education Survey (Hamilton et al, 2020), and still others were developed specifically for this survey.…”
Section: Survey Contentmentioning
confidence: 99%
“…NOTE: Items were adapted from the 2021 American Instructional Resources Survey(Doan et al, 2021). n = 1,504.…”
mentioning
confidence: 99%